A numerical study on dynamics behaviors of multi bubbles merger during nucleate boiling by lattice Boltzmann method. (September 2019) - Sun, Tao
Highlights: Merger bubble is found to cause higher heat transfer rate compared to single bubble. The highest heat transfer is obtained for four bubbles merging on superheated wall. Bubble merger increases the overall wall heat transfer by trapping a liquid layer. Formation of vapor bridges with liquid trapped underneath the bridges and vapor neck. Abstract: In this paper, bubble dynamics and multi bubbles merger associated with heat transfer are studied numerically by a three-dimensional hybrid lattice Boltzmann model. The dynamics behaviors of the vapor bubbles including growth, merger and departure on the superheated wall are simulated. Compared the numerical simulation results with experimental results available in references; it is found that the LBM simulations are in good agreement with existing results. The processes of multi bubbles merger show formation of vapor bridges with liquid trapped underneath the bridges and vapor neck before departure. The merger bubble is found to cause higher heat transfer rate compared to a single bubble. The highest wall heat transfer is obtained for four bubbles merging on the superheated wall. Bubble merger process increases the overall wall heat transfer by trapping a liquid layer between the bubble bases and by pulling cool liquid towards the wall during contraction.